2017
DOI: 10.4274/jus.783
|View full text |Cite
|
Sign up to set email alerts
|

Parameatal Urethral Cyst: A Case Report

Abstract: On yedi yaşında erkek hasta üretral meatusta 15 mm şişlik ile başvurdu. Değerlendirmede hasta işeme ile ilgili şikayet bildirmedi. Hasta kozmetik amaçlı tedavi arayışındaydı. Genç erkeklerde oldukça nadir görülen parameatal üretral kist benign bir durum olup literatürde olgu sayısı oldukça azdır. Kiste literatür önerisine uygun şekilde tam eksizyon uygulandı. Postoperatif takibinde hastanın hiçbir problemi olmadı. Anahtar Kelimeler: Olgu, kist, üretral meatus A 17-year-old boy presented with 15 mm swelling on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…In comparison, 20 % of others produced the symptoms of dysuria, urinary flow distortion, or pain in a ruptured cyst. The case of urinary retention in a 17-year-old patient with a parameatal cyst has also been reported by Vechiol et al [ 6 , 13 ]. Concerning this case series, the first patient came without any symptoms.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…In comparison, 20 % of others produced the symptoms of dysuria, urinary flow distortion, or pain in a ruptured cyst. The case of urinary retention in a 17-year-old patient with a parameatal cyst has also been reported by Vechiol et al [ 6 , 13 ]. Concerning this case series, the first patient came without any symptoms.…”
Section: Discussionsupporting
confidence: 61%
“…Parameatal cyst is more commonly found in children than adults, with a prevalence of 1–6 % in adult women [ 4 ]. Adult prevalence is rare, and <100 cases have been reported worldwide [ [4] , [5] , [6] ]. Until now, the cause of parameatal cyst is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The largest series was published by Willis et al in 2011, which reported 18 pre-pubertal boys. In addition to this series, Shiraki reported 9 cases in 1975 (Hodson et al, 2012;Saki et al, 2017;Tavukcu et al, 2017). Shiraki (1975) interpreted that this cyst may have formed from occlusion of the paraurethral duct or, in other cases, derived from incomplete preputial separation of the gland along the coronal sulcus (Yamada et al, 2013;Patil et al, 2015).…”
Section: Introductionmentioning
confidence: 79%
“…This condition is a rare case report, only less than 50 cases have been reported. The first case was reported by Thompson andLantin in 1956 (Shaw et al, 2018;Tavukcu et al, 2017;Oktaviani & Hoetama, 2020;Lal & Ankur, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation